Analisa Kesehatan Reproduksi Remaja Perempuan Usia Early Adolescence di Pekanbaru : Analysis of Reproductive Health of Adolescent Girls at Early Age Adolescence in Pekanbaru - Oswati Hasanah; Misrawati (Fakultas Keperawatan Universitas Andalas, 2013)
The purpose of this study was to obtain reproductive health in adolescent girls in Pekanbaru . The design used was a simple descriptive with cross-sectional approach. 189 respondents were selected by random cluster sampling technique. The result showed that majority of respondents are in the early adolescence age (79.9 % ) and most of them are Minangese (47.6 %). Based on the analysis related to breast health, the majority of respondents felt there is lump in their breast (80.4 %), but only 1.1 % of them have ever attempted to enlarge the breasts. Most respondents (63 %) have good habits in clothing, but more than a half have physiological vaginal discharge (55.6 %), almost all respondents have unhealthy habits in toiletting (97 %) and ever tried to overcome the flour albus (94.7 %) with a variety of herbs using traditional ingredients (79 %). It can be concluded in general the respondents still have a good reproductive health, but still required a sustained effort to maintain and improve the reproductive health status of adolescents in Pekanbaru.